2012
DOI: 10.1159/000338678
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Multiple Sclerosis in the General Population in the Netherlands, 1996–2008

Abstract: Background: We estimated the multiple sclerosis (MS) incidence in the Netherlands for better active monitoring of potential vaccine safety signals. Methods: A retrospective cohort study (1996–2008) was conducted using a population-based general practice research database containing electronic medical records. Additional information was collected to validate incident probable cases. Results: In the source population (648,656 persons), 146 incident probable MS cases were identified. Overall incidence rate was 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…The question about a gender ratio of GBS incidence therefore remains unsolved. Considering this, it is interesting to note that the incidence of multiple sclerosis, another autoimmune disorder, has increased particularly in women in Northern Finland (Krökki et al, ; Holmberg et al, ) and in the Netherlands (Kramer et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…The question about a gender ratio of GBS incidence therefore remains unsolved. Considering this, it is interesting to note that the incidence of multiple sclerosis, another autoimmune disorder, has increased particularly in women in Northern Finland (Krökki et al, ; Holmberg et al, ) and in the Netherlands (Kramer et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…In France, the national incidence was estimated to be 7.5 per 100,000 persons based on the main French insurance system [11]. In a Dutch study, incidence calculations based on a medical records database showed an increase of the IR from 4 per 100,000 PYs from 1996 to 2004 to 9 per 100,000 PYs in 2007 and 2008 [12]. Ahlgren et al[13] investigated the IR of MS in Sweden from 2001 to 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In the Sassari Province of Sardinia, incidence has increased from 1.1 to 5.8 between 1965-1969 and 1995-1999 [24]. Increasing incidence rates have also been reported in France [25], Netherlands [26], Australia [27], Japan [28], Finland [29], Norway [30,31] and Italy [32]. Interestingly, an increase in female-to-male ratio of MS incidence has also been observed, with a systematic review and meta-analysis estimating a ratio increase from 1.4 in 1955 to 2.3 in 2000 in incident cases, when incidence studies were repeated after some years or decades in the same population [33].…”
Section: Increasing Incidence Of Ms and T1dmentioning
confidence: 99%